Thermally Stable Anilate-Based 3D CPs/MOFs - Fabio Manna; Noemi Monni; Mariangela Oggianu; Juan Modesto Clemente-Juan; Miguel Clemente-León; Maria Laura Mercuri (Crystals)
The synthesis and characterization of two novel redox-active MOFs/CPs based on 3d transition metal ions and 3,6-ditriazolyl-2,5-dihydroxybenzoquinone (trz2An) are reported herein. By combining trz2An with NiII and MnII ions via the hydrothermal method, two phases, formulated as [Ni2(trz2An)2]·2.5H2O (1) and [Mn(trz2An)(H2O)]·1.5H2O (2), are obtained. Both compounds crystallize as neutral polymeric 3D frameworks, where the metal ions are coordinated through the oxygen atoms of the anilate linkers forming either straight (1) or zig-zag (2) 1D chains. In particular, (1) is a MOF, where these chains are connected through the nitrogen atom at the 4 position of the triazolyl group, which completes the coordination sphere of each metal ion, affording a 3D structure containing a void volume of 28.7% and voids that can be useful for the sorption of small molecules. Interestingly, (1) and (2) show a redox behavior due to the presence of the anilate linker, being reduced electrochemically in the −0.7 to −0.9 V range due to the benzoquinone–semiquinone one-electron reduction and magnetic behavior dominated by antiferromagnetic interactions in the anilate 1D chains.